Penerapan model project based learning dengan metode karya wisata dalam pembelajaran menulis teks deskripsi mata pelajaran bahasa jawa kelas x.3 SMA N 1 Juwana - Rosita, Andjelina Putri; Sulanjari, Bambang; Sunarya, Sunarya (Universitas PGRI Semarang, 2023)
This research aims to describe the results of applying the project-based learning model with the field trip method in learning to write Javanese descriptive text for class X.3 SMA N 1 Juwana. This is motivated by students who think that learning Javanese is a subject that is not interesting to study because of their lack of understanding of vocabulary and language. Apart from student factors, the main factor comes from teachers who experience limitations in implementing various learning models. Thus, the problem formulation obtained is the results of applying the PJBL model with the field trip method in learning to write descriptive texts.This research is included in pre-experimental design research in the form of a one shot case study. The approach used in this research is a descriptive quantitative approach, because the data obtained is calculated statistically and then the data is analyzed descriptively statistically, namely by describing the results of data calculations. The data collection used in this research was purposive sampling, while the data obtained in this research was collected by means of documentation and questionnaires.After data analysis, the following research results were obtained: 1) In the knowledge aspect, there were 31 students or 86% who obtained scores above the KKM, while 5 students or 14% had not yet reached the KKM. From this percentage, the completeness score obtained was 93.4. 2) In the skills aspect, 36 students or 100% have fulfilled the KKM that has been determined with a class average score of 90. Thus, the application of the pjbl model with the field trip method in learning to write Javanese descriptive texts for class X.3 SMA N 1 Juwana can have an influence on predetermined learning outcomes.